DETERMINASI INDEKS SAHAM SYARIAH - Rizki Afrinal (Veteran Economics, Management, & Accounting Review, 2024)
This study aims to determine the effect of international sharia stock indexes and macroeconomics on the price of the Jakarta Islamic Index. This study uses the Dow Jones Islamic Market World Index (DJIM), S&P 500 Shariah (SPSHX), and FTSE All-World Sharia Index (FTSES) as variables that represent international Islamic stock indices as well as interest rates (IR), inflation, and exchange rates. (ER) as a variable that represents Indonesia's macroeconomic conditions. Using the Vector Error Correction Model (VECM) method, this study shows that inflation, exchange rate, DJIM, SPSHX and FTSES have a significant influence on JII in the long term, whereas in the short term only inflation and interest rates have a significant effect on JII